Medication Administration Interruptions in a Rural Hospital and Evaluation of a Red Light Intervention - Trina Aguirre; Susan Wilhelm; Susan Backer; Susan Schoeneman; Ann Koehler (Rural Nurse Organization; Binghamton University, 2015)
Purpose:  This study was conducted to determine the prevalence and types of interruptions nurses experience during the peak medication administration period (weekdays 7:00 AM-9:00 AM) at a rural regional hospital and to evaluate the effectiveness of a red light intervention to reduce interruptions. Sample:  Participants were a convenience sample of registered nurses who agreed to be observed administering medications. The same nurses were observed during both phases of the study. Methods:  This study employed a prospective exploratory design.  The same observation procedures were used during both phases of the study.  During each 2-hour observation period, each participating nurse was accompanied by two observers who recorded all interruptions.  During the intervention, a small flashing red light was attached to the medication administration computer.  When turned on it served as a signal to avoid interruptions.  Educational flyers were distributed to staff, physicians, patients, and visitors to inform them about the meaning of the light. Findings:  Average interruptions per 2-hour medication administration period dropped from an average of 7.2 during baseline to 3.0 during the red light intervention. The top two source of interruptions during both phases were other personnel and not having needed medical supplies/equipment, though the rankings were reversed. The relative prevalence of interruptions caused by other personnel declined from 27.6% (baseline) to 21.8% (intervention).     Conclusions:  The major categories of interruptions at this rural regional acute care hospital were similar to those identified in studies in urban settings.  The red light intervention effectively reduced the average number of interruptions per 2-hour period and reduced the incidence of interruptions caused by other personnel.  The prevalence of interruptions due to missing supplies/equipment remained high and should be addressed by implementing procedures to ensure that carts are appropriately stocked.  DOI: http://dx.doi.org/10.14574/ojrnhc.v15i2.327  Keywords:  Medication administration,  Interruptions, Rural